Gamification-Based Learning Design with Wordwall to Improve Learning Activities and Learning Outcomes - Panis, Isabel Coryunitha; Ki'i, Oktavianus Ama; Juan, Fransiskus Andi; Freitas, Maria Lia Felizarda (Universitas Pendidikan Ganesha, 2025)
Information and communication technology has brought about major changes in education, including more creative and engaging ways of teaching for students. Gamification, the application of game elements to non-game contexts, such as learning in schools, is a method that is starting to be widely used. This method is considered capable of increasing student engagement, motivation, and learning outcomes. However, media gamification in junior high school learning still faces many problems that need to be considered carefully. This study aims to (1) analyze student abilities as viewed from student activities when using Wordwall-assisted gamification learning design and (2) analyze student abilities as viewed from student learning outcomes after implementing Wordwall-assisted gamification learning design. This study uses the pre-experimental designs (non-designs) method with a one-group pretest-posttest design. The results of the study indicated that this media design met the eligibility criteria with a validity score of 0.67. The observation of student activities yielded an average score of 85.67%, placing it in the very high category. Apart from that, gamification-based learning with Wordwall also improves student learning outcomes, with an N-Gain value of 0.726, which is classified as high. The average initial test score of 31.5 increased to 80.3 in the final test, which shows a significant increase in student learning achievement. The results indicate that Wordwall media, which is designed with gamification principles, improves student learning outcomes and increases their learning activities. This makes learning more interactive and fun and encourages students to participate more actively in it.